Combining biomimetic principles from the lotus leaf and mussel adhesive: polystyrene films with superhydrophobic and adhesive layers - Neto, Ana I. (2013)
Lotus leaves are well known for their extremely water repellent surfaces. Marine mussels are also a popular research topic when considering biological adhesives. Both organisms have inspired the development of several biomimetic materials. Herein we describe a two-sided film made almost entirely from polystyrene onto which the properties of both lotus leaves and mussel adhesive are incorporated. On one side of the film, imparting micrometer and nanometer scale hierarchical roughness yields superhydrophobicity and water repellency, which facilitates rapid fluid flow. The other side of the film is modified with a copolymer mimic of 3,4-dihydroxyphenylalanine (DOPA)-containing mussel adhesive proteins. This copolymer incorporates 3,4-dihydroxystyrene, to represent DOPA, randomly into a polystyrene host polymer. The flexibility of the polystyrene backing film enabled rolling of the assembly into a tubular shape. Inside the polystyrene tube was the superhydrophobic lotus mimic. The mussel adhesive mimic, on the outer layer, was used to glue the tube to itself, thus maintaining the tubular shape. The film was also successfully glued to a variety of flat substrates. These two-dimensional and three-dimensional assemblies can be used to direct and localize the flow of fluids, with partitioning between superhydrophobic and relatively hydrophilic regions. Such assemblies may facilitate the design of liquid transport for industrial and biomedical devices .